Endoscopic and Histopathologic Findings Associated with H-pylori Infection in Very Young Children - ERTEM ŞAHİNOĞLU, DENİZ; TUTAR, ENGİN (SPRINGER, 2009)
Most of the individuals infected with H. pylori acquire the infection early in life. However, there is limited data regarding endoscopic and histopathologic findings of H. pylori infection when it is acquired during infancy. The aim of this study was to investigate the H. pylori-related endoscopic and histopathological findings in children younger than 2 years of age. One hundred and fifty-two infants who underwent upper gastrointestinal endoscopy were included in the study. The diagnosis of H. pylori infection was based on histopathology and a positive rapid urease test. Forty of 152 (26.3%) infants were infected with H. pylori, and 65% of the infected infants had histopathologic gastritis. There were no clinical or endoscopic findings suggestive of H. pylori infection. No correlation could be found between the density of H. pylori and the severity of gastritis. H. pylori infection is associated with various degrees of gastritis in more than half of the infected infants. Since the likelihood of normal histopathology is rare in H. pylori-infected infants, its long-term complications should be cautiously followed up in endemic areas.
Keywords: H; pylori; Children; Endoscopy; Histopathology; RECURRENT ABDOMINAL-PAIN; GASTROESOPHAGEAL-REFLUX DISEASE; GASTRIC ATROPHY; PEPTIC-ULCER; PEDIATRIC-GASTROENTEROLOGY; WORKING GROUP; INFANTS; INFLAMMATION; ADOLESCENTS; SYMPTOMS